Digital-Based Young Entrepreneur Development Model - Mulyadi, Hari; Supardi, Endang; Waspada, Ikaputra; Ramdhani, Arief; Lubis, Asep Ridwan; NH, Nabil Fatya (Fakultas Kewirausahaan Universitas Garut, 2026)
This study aims to develop a model for digital-based youth entrepreneurship through the activities of Karang Taruna Indonesia (KTI) in Melong Village, South Cimahi District, Cimahi City. Using a descriptive qualitative approach with research and development (R&D) methods, this study combines field observations, interviews, and focus group discussions with members and administrators of Karang Taruna. The findings show that entrepreneurial activities within KTI are still conventional and have not been integrated with digital marketing platforms. The developed model emphasizes three components: input, process, and output, which include training, mentoring, and digital literacy enhancement. Validation results from experts and practitioners indicate that the model is feasible for implementation and can be used as a reference for developing youth entrepreneurship in other community organizations.